2023
DOI: 10.3389/fcell.2023.1186526
|View full text |Cite
|
Sign up to set email alerts
|

Fgf8 regulates first pharyngeal arch segmentation through pouch-cleft interactions

Abstract: Introduction: The pharyngeal arches are transient developmental structures that, in vertebrates, give rise to tissues of the head and neck. A critical process underlying the specification of distinct arch derivatives is segmentation of the arches along the anterior-posterior axis. Formation of ectodermal-endodermal interfaces is a key mediator of this process, and although it is essential, mechanisms regulating the establishment of these interfaces vary between pouches and between taxa.Methods: Here, we focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 63 publications
(123 reference statements)
1
5
0
Order By: Relevance
“…Given established roles for Fgf8 and Fgf3 signalling in the control of pharyngeal pouch development or morphogenesis in zebrafish ( Crump et al, 2004 ), lamprey ( Jandzik et al, 2014 ) and mouse ( Zbasnik and Fish, 2023 ), we examined spatial expression of Fgf8 and Fgf3 by mRNA in situ hybridisation during skate gill slit development. We found that discrete Fgf8 expression domains appear in a rostral-to-caudal sequence, in the vicinity of each developing pharyngeal pouch, from S18–S22 ( Fig.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Given established roles for Fgf8 and Fgf3 signalling in the control of pharyngeal pouch development or morphogenesis in zebrafish ( Crump et al, 2004 ), lamprey ( Jandzik et al, 2014 ) and mouse ( Zbasnik and Fish, 2023 ), we examined spatial expression of Fgf8 and Fgf3 by mRNA in situ hybridisation during skate gill slit development. We found that discrete Fgf8 expression domains appear in a rostral-to-caudal sequence, in the vicinity of each developing pharyngeal pouch, from S18–S22 ( Fig.…”
Section: Resultssupporting
confidence: 68%
“…But unlike in zebrafish, where pharyngeal pouches fail to form in the absence of Fgf signalling, formation of the first pharyngeal pouch in mouse appears to be laregly robust to reductions in Fgf8 dosage. Instead, Fgf8 signalling is required in mouse for separation of the mandibular and hyoid arches via reshaping and elongation of the first pharyngeal pouch and interaction of this pouch with adjacent ectoderm ( Zbasnik and Fish, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given established roles for Fgf8 and Fgf3 signalling in the control of pharyngeal pouch development or morphogenesis in zebrafish (Crump et al, 2004), lamprey (Jandzik et al, 2014) and mouse (Zbasnik, 2023), we examined spatial expression of Fgf8 and Fgf3 by mRNA in situ hybridisation during skate gill slit development. We found that discrete Fgf8 expression domains appear in a rostral-to-caudal sequence, in the vicinity of each developing pharyngeal pouch, from S18-S22 (Fig.…”
Section: Expression Of Fgf8 and Fgf3 During Gill Slit Development In ...mentioning
confidence: 99%
“…In the lamprey, Fgf3 and Fgf8 are expressed in the posterior region of each pharyngeal endodermal pouch with Fgf8 additionally expressed in overlying pharyngeal ectoderm (Jandzik et al, 2014), and this regionalised expression of Fgf8 and/or Fgf3 within pharyngeal endormal pouches is conserved in chick (Veitch et al, 1999) and skate (reported here). In mouse Fgf8 is expressed broadly throughout pharyngeal pouch endoderm and in overlying ectoderm, as well as in splanchnic mesoderm (Abu-Issa et al, 2002;Zbasnik et al, 2023), while in zebrafish fgf8 is expressed in pharyngeal mesoderm during pouch formation (Choe and Crump, 2014).…”
Section: Fgf Signalling and Vertebrate Pharyngeal Pouch Developmentmentioning
confidence: 99%
See 1 more Smart Citation